2016
DOI: 10.1007/s11011-016-9794-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacological characterization of the oneirogenic Mexican plant Calea zacatechichi aqueous extract in mice

Abstract: This study evaluates the neuropharmacological effects of the aqueous extract of the Mexican plant Calea zacatechichi Schltdl., which is commonly used in folk medicine to treat cough, asthma, and gastrointestinal disorders. Moreover, it has been used for centuries in traditional rituals based on divination and is thought to possess hallucinogenic activity. To test the neuropharmacological effects of the aqueous extract of C. zacatechichi we used mouse models of convulsions, an elevated plus-maze test and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Thus, the organic extract was not toxic according to the Lorke criteria. These outcomes are consistent with the safe ancestral consumption of this indigenous species and the lack of neuropharmacological effects observed by Salaga and coworkers [ 9 ]. It will be appropriated, however, to subject this plant to normal pharmacovigilance practices to provide assurance of its long-term innocuity.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the organic extract was not toxic according to the Lorke criteria. These outcomes are consistent with the safe ancestral consumption of this indigenous species and the lack of neuropharmacological effects observed by Salaga and coworkers [ 9 ]. It will be appropriated, however, to subject this plant to normal pharmacovigilance practices to provide assurance of its long-term innocuity.…”
Section: Resultssupporting
confidence: 92%
“…Previous pharmacological investigations showed that the plant exhibited antiinflammatory [ 4 , 5 ], antiplasmodial [ 6 ], antileshimanial [ 7 ], antimicrobial, antidiarrheal and antinociceptive effects [ 8 ]. Recent neuropharmacological evaluation of an aqueous extract of C. ternifolia using the mouse models of convulsion, forced swim, elevated plus-maze, muscular strength in a grip and locomotor tests, revealed that the aqueous extract had not significant effects in these assays [ 9 ]. However, an organic extract of this herb displayed significant cytotoxicity against human proximal tubule HK-2 cells and increased the level of nephrotoxicity biomarkers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was not observed influence in anxiety, exploratory behavior, muscular strength, and centrally mediated antinociception. However, a statistically significant antinociceptive action (200 mg·kg −1 , p < .05) was detected in acetic acid induced writhing test (Salaga et al, ).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Further, Calea zacatechichi Schltdl. species is commonly used in Mexico as cholestatic, cathartic, antidiarrheal, antidiabetic, psychotropic (Hernandez‐Galicia et al, ; Mayagoitia, Diaz, & Contreras, ; Salaga et al, ; Zamora‐Martinez & Pola, ), and to treat inflammation‐related diseases (rheumatism and edema) and respiratory problems (asthma and cough; Salaga, Kowalczuk, Zielinska, Blazewick, & Fichna, ; Venegas‐Flores, Segura‐Cobos, & Vazquez‐Cruz, ). El Salvador's population uses Calea urticifolia (Mill.)…”
Section: Introductionmentioning
confidence: 99%
“…For this, C. ternifolia is used in several countries, although it was placed on the prohibited plant list in Poland in 2013 [4]. A more recent study of the neuropharmacological action of the aqueous extract of C. zacatechichi indicates that it has insignificant neuropharmacological effects and also reduces the abdominal pain perception [5]. It is also traditionally used for the treatment of endocrine and gastrointestinal problems [6].…”
Section: Introductionmentioning
confidence: 99%